Pilot Test of a DBT-Based Parenting Intervention for Parents of Youth With Recent Self-Harm. Issue 2 (May 2022) - Berk, Michele S.; Rathus, Jill; Kessler, Moira; Clarke, Stephanie; Chick, Christina; Shen, Hanyang; Llewellyn, Tanya
Highlights: Improving family functioning is a critical target of interventions for youth with self-harm (SH). We developed a brief, DBT-based, parent-only intervention for parents of youth with recent SH. The intervention was feasible and acceptable, and reductions in parent depression, emotion dysregulation and caregiver strain were observed. Decreases in youth SH were also observed. Results support further testing of the intervention. A description of the treatment and case examples are provided. Abstract: Improving family functioning is a critical treatment target for youth at risk for suicide. The present study focused on the development and pilot testing of a brief, parent-only, Dialectical Behavior Therapy (DBT)-based intervention with N  = 10 sets of parents of youth with a suicide attempt or nonsuicidal self-injury within the past 3 months. Youth received treatment as usual; however, they did not receive any treatment as part of the study. Results showed that parents who received the intervention reported reductions in parent self-reported depressive symptoms, emotion dysregulation, caregiver strain, psychiatric symptom distress and interpersonal sensitivity, from baseline to 6-month follow-up. Youth also showed decreases in total self-harm from baseline to 6-month follow-up. These results provide support for further testing of the DBT-based parenting intervention, both as a stand-alone treatment and as an adjunct to enhance the effectiveness of standard DBT for adolescents. This article provides a detailed description of the parenting protocol, as well as a case example.